CO2 drawdown following the middle Miocene expansion of the Antarctic Ice Sheet. (22nd March 2013) - Badger, Marcus P. S.; Lear, Caroline H.; Pancost, Richard D.; Foster, Gavin L.; Bailey, Trevor R.; Leng, Melanie J.; Abels, Hemmo A.
Abstract : [1] The development of a permanent, stable ice sheet in East Antarctica happened during the middle Miocene, about 14 million years (Myr) ago. The middle Miocene therefore represents one of the distinct phases of rapid change in the transition from the "greenhouse" of the early Eocene to the "icehouse" of the present day. Carbonate carbon isotope records of the period immediately following the main stage of ice sheet development reveal a major perturbation in the carbon system, represented by the positive δ 13 C excursion known as carbon maximum 6 ("CM6"), which has traditionally been interpreted as reflecting increased burial of organic matter and atmospheric p CO2 drawdown. More recently, it has been suggested that the δ 13 C excursion records a negative feedback resulting from the reduction of silicate weathering and an increase in atmospheric p CO2 . Here we present high‐resolution multi‐proxy (alkenone carbon and foraminiferal boron isotope) records of atmospheric carbon dioxide and sea surface temperature across CM6. Similar to previously published records spanning this interval, our records document a world of generally low (~300 ppm) atmospheric p CO2 at a time generally accepted to be much warmer than today. Crucially, they also reveal a p CO2 decrease with associated cooling, which demonstrates that the carbon burial hypothesis for CM6 is feasible and could have acted as a positive feedback on global cooling. Key Points: middle Miocene atmospheric CO2 is low (~300 ppm) Atmospheric CO2 declined over carbon maximum 6 Organic carbon burial is a possible positive feedback for ice sheet growth